The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jtxs.12127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Healthy Sweeteners (Tagatose and Oligofructose) on the Physicochemical Characteristics of Orange Marmalade

Abstract: Today's society shows a growing interest in healthy, safe and high nutritional quality food. Thus, in this paper sweet orange marmalades have been developed using healthy sweeteners (tagatose and oligofructose) in different proportions. Analyses of Brix, pH, moisture, water activity, antioxidant capacity, optical and rheological properties have been carried out, initially and after 45 days of storage. Microbiological analyses have also been performed to determine their stability. Furthermore, a sensorial asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…In contrast, the results for marmalade C were most similar to the results for the control marmalade, most likely due to the analogous chemical structure of the sucrose and isomaltulose molecules. However, in our previous work (RUBIO-ARRAEZ et al, 2015) carried out on orange marmalade formulated with oligofructose and tagatose as a substitutes for sucrose, there was an increase in the elastic component (G') after 45 days of storage. Consequently, it can be concluded that depending on the nature of the chemical structure of the sweetener used, the rheological behaviour will be different.…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the results for marmalade C were most similar to the results for the control marmalade, most likely due to the analogous chemical structure of the sucrose and isomaltulose molecules. However, in our previous work (RUBIO-ARRAEZ et al, 2015) carried out on orange marmalade formulated with oligofructose and tagatose as a substitutes for sucrose, there was an increase in the elastic component (G') after 45 days of storage. Consequently, it can be concluded that depending on the nature of the chemical structure of the sweetener used, the rheological behaviour will be different.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…The rheological properties of the mandarin orange marmalades studied were analysed using a controlled stress rheometer manufactured by Thermo Fisher Scientifi c, Inc. (Haake RheoStress 1, Waltham, Massachusetts, USA), at 25 ºC, using the protocol described in previous studies (PEINADO et al, 2012;RUBIO-ARRAEZ et al, 2015). Oscillatory or steady-state tests were carried out to study the pseudoplastic or viscoelastic behaviour of marmalades, respectively.…”
Section: Rheological Analysismentioning
confidence: 99%
See 3 more Smart Citations